Cost-Effectiveness Analysis of Ultrasound Screening for Thyroid Cancer in Asymptomatic Adults - Yang, Nan; Yang, Han; Guo, Jeff Jianfei; Hu, Ming; Li, Sheyu (Frontiers in Public Health, 2021)
Objectives: This study was aimed to evaluate the long-term cost-effectiveness of ultrasound screening compared with non-screening in asymptomatic population to provides informative input for health care decision makers to develop relevant guidelines for thyroid cancer management strategy. Methods: Applying a Markov decision-tree model, we compared the long-term cost effectiveness of the two strategies: screening and non-screening. Efficacy and cost data in this study were derived from the literature. A one-way sensitivity analysis and a probabilistic sensitivity analysis were performed to verify the stability of model results. Results: The cumulative cost of screening for thyroid cancer was 18,819.24, with 18.73508 quality-adjusted life years (QALYs), whereas the cumulative cost of non-screening was 15,864.28, with 18.71 QALYs. The Incremental Cost-Effectiveness Ratio of 106,947.50/QALYgreatly exceeded the threshold of 50,000. The result of the one-way sensitivity analysis showed that the utility values of benign nodules and utility of health after thyroid cancer surgery would affect the results. Conclusions: Ultrasound screening of thyroid cancer has no obvious advantage in terms of cost-effectiveness compared with non-screening, which does not mean that thyroid cancer screening is completely useless. The optimized thyroid screening guideline for a specific population or subgroups should be released.